Influence of equal-channel angular pressing on the microstructure and corrosion behaviour of a 6xxx aluminium alloy for automotive conductors. (15th April 2020) - Rochet, C.; Veron, M.; Rauch, E.F.; Lowe, T.C.; Arfaei, B.; Laurino, A.; Harouard, J.P.; Blanc, C.
Graphical abstract: Highlights: ECAP induced grain refinement and increased HABG density. Pits were more numerous in ECAP samples due to Fe-rich IMCs fragmentation. After ECAP, lateral pit growth was promoted by a high amount of HAGBs around IMCs. ECAP promoted lateral pit growth rather than in-depth propagation. Coalescing pits were often observed for ECAP samples. Abstract: An Al-Mg-Si aluminium alloy was shaped by using a two-pass equal-channel angular pressing (ECAP) process. This led to fragmentation of the coarse Fe-rich intermetallics (IMCs), a decrease in grain size and an increase in the high angle grain boundary (HAGB) density, with overconcentration of HAGBs around the IMCs. Corrosion tests in NaCl solution showed that, before and after ECAP, only pitting corrosion occurred. However, for ECAP samples, pits were more numerous due to the fragmentation of the IMCs; they were also larger and less deep, their propagation being strongly influenced by the presence of very small grains around the IMCs.